Infographics between figures and figurative language - Giacomo Festi (Signata, 2019)
This contribution critically examines the relevance of infographics for semiotic research, especially insofar as perception and cognition are concerned. After a theoretical discussion of the debate that animates graphic designers themselves, and rereading the classic contribution of Tufte about data display, the essay cross-compares three different cases of infographics, from three different angles, using a corpus mainly referring to two magazines, the Italian La Lettura and the Italian version of Wired. The first concerns the narrative/argumentative relationship between the verbal paratext and the visual data inside the infographics, showing the manipulative role of the data distribution itself within a unique infographic investigation, which is analyzed in depth. The second angle is that of the strategy of visualization and its connection with the diverse cognitive operations such as individuation, comparison, correlation and exploration, arriving at a form of schematization that uses the tension between perceptual salience and the extension of cognitive activity. The final approach is about a trend in infographics, the introduction of a figurative further layer of visualization. The treatment of that figurative level impacts on the tone of the image, with examples that display dramatic, lyrical, pedagogical or ironical treatments. Thanks to the figurative dimension, affection is made present inside the typically cold language of data, along with perception and cognition.